2010
DOI: 10.3109/10715762.2010.522576
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive limb ischemic pre-conditioning reduces oxidative stress and attenuates myocardium ischemia-reperfusion injury in diabetic rats

Abstract: This study was to explore whether repeated non-invasive limb ischemic pre-conditioning (NLIP) can confer an equivalent cardioprotection against myocardial ischemia-reperfusion (I/R) injury in acute diabetic rats to the extent of conventional myocardial ischemic pre-conditioning (MIP) and whether or not the delayed protection of NLIP is mediated by reducing myocardial oxidative stress after ischemia-reperfusion. Streptozotocin-induced diabetic rats were randomized to four groups: Sham group, the I/R group, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Zhu et al (2011b) found that the diabetic rat heart in vivo was amenable to infarct size reduction elicited by limb preconditioning (3 Â 5-minute cycles of hindlimb cuff inflation/deflation). However, it is important to note that in this study streptozotocin-induced diabetes was only initiated 1 week before MI.…”
Section: Diabetesmentioning
confidence: 99%
“…Zhu et al (2011b) found that the diabetic rat heart in vivo was amenable to infarct size reduction elicited by limb preconditioning (3 Â 5-minute cycles of hindlimb cuff inflation/deflation). However, it is important to note that in this study streptozotocin-induced diabetes was only initiated 1 week before MI.…”
Section: Diabetesmentioning
confidence: 99%
“…However, NLIP is less efficacious in certain pathological states, such as diabetes, senescence and obesity. Interestingly, we showed that application of 3 cycles of NLIP per day for 3 days (repeated NLIP, rNLIP) attenuated myocardial I/RI in diabetic rats [11-13], suggesting that, in order to confer cardioprotection under pathological conditions, the threshold of NLIP should be increased. However, the mechanism whereby rNLIP may confer cardioprotection in diabetes is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that rNLIP conferred cardioprotection in diabetic rats [11] whose cardiac STAT3 was initially reduced [15]. It is possible, therefore, that enhancing cardiac STAT3 activation may be a mechanism to restore rNLIP in diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Lujan et al reported that partial hind limb occlusion reduced the susceptibility to sustained ventricular tachycardia in conscious rats [22]. Moreover, Zhu et al found that LIPC can confer similar cardioprotection from myocardial I/R injury in acute diabetic rats to the extent of conventional MIPC [23].…”
Section: Discussionmentioning
confidence: 97%